THE INFLUENCE OF MARKETING AND PROMOTION ON PURCHASING DECISIONS THROUGH TIKTOK SOCIAL MEDIA ON NAJWA FRUIT SALAD DESSERT AT LAKARSANTRI SURABAYA - Wardatus Azka Assanada; Is Fadhilah (Pedagogic Research-Applied Literacy Journal, 2025)
This study investigates the influence of marketing and promotion through TikTok on purchasing decisions for Najwa Fruit Salad Dessert in Lakarsantri. Using a quantitative approach, data was collected from consumers via questionnaires and analyzed with SPSS version 20. The results show that the Marketing variable (X1) has a positive and significant effect on Purchasing Decisions (Y). However, the Social Media variable (X2) shows a negative and insignificant effect when tested partially. Simultaneously, Marketing and Social Media variables significantly influence purchasing decisions. This highlights the importance of effective marketing strategies to boost consumer buying behavior through TikTok.